School Cluster policy in Portugal: elements of the sociology of organizations for the study of a new normative model of school organization - Bocchio, María Cecilia (2016)
This article presents results of a doctoral thesis framed in the Portuguese educational policy of School Clusters (SC). Since 2010, the SC represents a new regulatory model of school organization that brings together multiple schools, at all levels of compulsory education and located in geographic proximity. Specifically, this research approaches this policy enactment in an SC located in Lisbon. The theoretical and methodological approach of the study is based on the contributions that Erhard Friedberg developed within the framework of the sociology of organizations. The publication is divided in two sections. First, the article introduces the SC policy and research carried out for this article. Then, the second section addresses Friedberg’s core conceptual categories. His concept of Concrete Action System allows analyzing through which actors and how the action is organized in the fictitiously named SC Margin. It is intended to show the potential that the sociology of organizations has for research in education policy, particularly in the study of complex regulatory processes of educational policies that occur in educational institutions.